PMO-113 FN14 is expressed on cholangiocytes and promotes biliary ductular remodelling via apoptosis and reactive oxygen species after interaction with tweak. (28th May 2012) - Stephenson, B; Humphreys, E; Muirhead, G; Wilhelm, A; Munir, M; Burkly, L; Adams, D; Afford, S
Abstract : Introduction: The mortality from chronic liver disease in the UK has increased by 50%. 1 The prevalence of cholangiopathies, diseases of the bile ducts, has increased fourfold. 2 These include primary biliary cirrhosis, primary sclerosing cholangitis and allograft rejection after transplantation. 3 4 It is increasingly observed in livers donated for transplantation after cardiac death, a source of organs on which the NHS is becoming more reliant. 5 6 It is characterised by inflammation and destruction of intrahepatic bile ducts. 7 When sustained it may drive portal fibrosis to end-stage liver disease when the only therapeutic option for patients is liver transplantation. 8 The novel TNF superfamily member TNF-like weak inducer of apoptosis (TWEAK) and its cognate receptor FGF-inducible protein 14 (Fn14) are implicated in hepatic inflammation and remodelling. 9 10 TWEAK is mainly secreted as a soluble cytokine by myelomonocytic cells. 11 Fn14-TWEAK interaction in other systems promotes cell growth, apoptosis, autophagy and transdifferentiation via activation of TRAF and NF-kB pathways. 12 Aim: To demonstrate the expression of Fn14 and TWEAK on cholangiocytes and the functional significance of Fn14/TWEAK interaction on biliary ductular remodelling. Methods: Human liver samples were obtained with consent from the Queen Elizabeth Hospital liver transplant programme. Sections were stained for Fn14 and TWEAK using immunohistochemical techniques. Expression of Fn14 and TWEAK on cholangiocytes stimulated with TNF-α, IFN-γ and FGF was established quantitatively using flow cytometry. Cholangiocytes stimulated with FGF were exposed to TWEAK for 48 h. Apoptosis and reactive oxygen species production at this time point were determined by flow cytometry using annexin and dichlorofluorescein assays respectively. Results: Immunohistochemistry reveals Fn14 on the intra-hepatic small bile ducts of inflamed livers, especially around the Canals of Hering. Fn14 expression is increased on cholangiocytes in vitro by 26% after stimulation with FGF. Exposure of cholangiocytes to TWEAK for 48 h induces apoptosis and upregulation of reactive oxygen species in FGF-activated cholangiocytes. Conclusion: Fn14 is expressed on cholangiocytes in inflamed human livers. Activation of the Fn14/TWEAK receptor-ligand system induces apoptosis using a novel mechanism partly dependent on the generation of reactive oxygen species. Competing interests: None declared. References: 1. Williams JG, Roberts SE, Ali MF, et al. Gastroenterology services in the UK. The burden of disease, and the organisation and delivery of services for gastrointestinal and liver disorders: a review of the evidence. Gut 2007;56 (Suppl 1):1–113. 2. James OF, Bhopal R, Howel D, et al. Primary biliary cirrhosis once rare, now common in the United Kingdom? Hepatology 1999;30 :390–4. 3. Burt AD . Primary biliary cirrhosis and other ductopenic diseases. Clin Liver Dis 2002;6 :363–80, vi. 4. Polson J, Lee WM; American Association for the Study of Liver Disease. AASLD position paper: the management of acute liver failure. Hepatology 2005;41 :1179–97. 5. Foley DP, Fernandez LA, Leverson G, et al. Biliary complications after liver transplantation from donation after cardiac death donors: an analysis of risk factors and long-term outcomes from a single center. Ann Surg 2011;253 :817–25. 6. NHSBT Monthly Statistics . 2011. 7. Desmet VJ . Histopathology of chronic cholestasis and adult ductopenic syndrome. J Clin Liver Dis 1998;2 :249–64, viii. 8. Eksteen B, Afford SC, Wigmore SJ, Immune-mediated liver injury. Semin Liver Dis 2007;27 :351–66. 9. Jakubowski A, Ambrose C, Parr M, et al. TWEAK induces liver progenitor cell proliferation. J Clin Invest 2005;115 :2330–40. 10. Tirnitz-Parker JE, Viebahn CS, Jakubowski A, et al. Tumor necrosis factor-like weak inducer of apoptosis is a mitogen for liver progenitor cells. Hepatolog y. 2010;52 :291–302. 11. Kaduka Y, Takeda K, Nakayama M. TWEAK mediates anti-tumor effect of tumor-infiltrating macrophage. Biochem Biophys Res Commun . 2005;331 :384–90. 12. Roos C, Wicovsky A, Müller N, et al. Soluble and transmembrane TNF-like weak inducer of apoptosis differentially activate the classical and noncanonical NF-kappa B pathway. J Immunol 2010;185 :1593–605.